Validity-reliability of the e-Healthy Diet Literacy Scale in Turkish adults - Sevil Karahan Yılmaz; Gunay Eskici; Osman Emir Sarac (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: This study aims to establish the validity-reliability of the Turkish version of adult e-Healthy Diet Literacy Scale and to determine its relationship with the Health Literacy Instrument Scale (short-form), the Digital Healthy Diet Literacy Scale, and participants' characteristics. Material and Methods: Drawing on a methodological and descriptive design, this research was performed in two steps. It was conducted with 240 participants in the first step and 879 participants in the second step. The participants filled out the eHealthy Diet Literacy Scale, Health Literacy Instrument Scale (short-form), and Digital Healthy Diet Literacy Scale. The questionnaire form was sent to the participants online. Results: Cronbach's alpha coefficient for the 11-item e-Healthy Diet Literacy scale was found to be 0.555. There was a significant relationship between the Health Literacy Instrument Scale (short-Form) and age groups, educational level, occupations, marital status, BMI, weekly physical activity and chronic disease status. Conclusions: This study evaluated the Turkish validity and reliability of the e-HDL, which was originally designed in Taiwan as a valid and reliable tool to evaluate the individuals' ability to access, understand, appraise, and apply healthy diet information.